Ḥaflat al-Mawlid al-Nabawī wa-Qirā’at Kitāb al-Barzanjī fī Mujtama‘ Sasak: Manẓūrāt Tārīkhīyah - Jamaluddin, Jamaluddin (Studia Islamika, 2011)
Sasak Muslims believed that maulid (Rabiul Awwal) month is a noble month and the best month to carry out syukuran (thankfulness) celebration or other religious rituals activities. Therefore, practices such as ngurisang (hair shaving for babies), nyunatang (circumcision for boys), namatang (completing the Qur'an reading), and merarik (marriage) are mostly performed in the maulid month. In its development then, the Kitab Barzanji reading within Sasak Muslims is not only observed in the maulid celebration, but also in many religious and traditional activities which are performed outside the maulid month. Some of the examples are the besok tian or tujuh bulanan tradition (a ceremony for women whose pregnancy age is seven months), ngurisang (hair shaving for babies), which is usually coupled with aqiqah, nyunatang (circumcision for boys), beserakal (reading the Kitab Barzanji to pray ones who will pilgrimage). Although the ritual is practiced not in the maulid month, the reading tradition of Kitab Barzanji in these ceremonies is relentlessly important. In the southern part of Lombok, the Kitab Barzanji reading has been performed on every Friday night, usually called kelaman ceremony. Sasak people experience shows that the maulid and the Kitab Barzanji reading has become a tradition practiced continuously from one to the next generation since this tradition introduced to Lombok.DOI: 10.15408/sdi.v18i2.436